2022
DOI: 10.3389/fimmu.2022.962341
|View full text |Cite
|
Sign up to set email alerts
|

The anti-obesity effects of a water-soluble glucan from Grifola frondosa via the modulation of chronic inflammation

Abstract: Polysaccharides from Grifola frondosa (G. frondosa) have anti-obesity and anti-inflammatory activities. In this study, the major type, molecular weight, homogeneity and structure of a polysaccharide purified from G. frondosa (denoted GFPA) were determined. In high-fat diet (HFD)-treated mice, 8 weeks of GFPA administration efficiently decreased body weight and blood glucose concentration and counteracted hyperlipidemia. GFPA efficiently decreased adipocyte size and ameliorated inflammatory infiltration in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…As the two largest taxonomic phylum in the intestinal microbiota, the increase in the ratio of Firmicutes to Bacteroidetes (F/B) is generally considered to be related to obesity ( 44 ). Two recent reports have shown that either G. frondosa polysaccharide or direct feeding G. frondosa can regulate lipid metabolism, reduce body weight, and is related to the TLR4/NF-κB signaling pathway ( 45 , 46 ). In this research, the weight growth trend of mice after low, middle, and high doses of GFPS intervention decreased, which also proved this point.…”
Section: Discussionmentioning
confidence: 99%
“…As the two largest taxonomic phylum in the intestinal microbiota, the increase in the ratio of Firmicutes to Bacteroidetes (F/B) is generally considered to be related to obesity ( 44 ). Two recent reports have shown that either G. frondosa polysaccharide or direct feeding G. frondosa can regulate lipid metabolism, reduce body weight, and is related to the TLR4/NF-κB signaling pathway ( 45 , 46 ). In this research, the weight growth trend of mice after low, middle, and high doses of GFPS intervention decreased, which also proved this point.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicated that moderate intake of β‐glucan was beneficial to the human intestine and mitigated damage to the intestine during inflammation via exerting antioxidant and anti‐inflammatory properties 34‐36 . Soluble glucan from Grifola frondosa also reduced high fat diet induced TLR4/NF‐κB signal pathway activation and exerted anti‐obesity effect 37 . As a well‐known gut microbiota modulator, β‐glucan could exhibit various functions via improving microbiota abundance.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] Soluble glucan from Grifola frondosa also reduced high fat diet induced TLR4/NF-κB signal pathway activation and exerted anti-obesity effect. 37 As a wellknown gut microbiota modulator, ⊎-glucan could exhibit various functions via improving microbiota abundance. Oat ⊎-glucan supplementation reduced serum level of pro-inflammatory factors such as TNF-⊍, interleukin-1⊎ (IL-1⊎), and lipopolysaccharide (LPS) by modulating gut microbial composition.…”
Section: Discussionmentioning
confidence: 99%
“…26 The M w and homogeneity of PAPS2 were determined using a gel permeation chromatography system coupled online to a multi-angle laser light scattering system. 27 The monosaccharide components of the hydrolyzed PAPS2 were detected using a high-performance liquid chromatography system. 25 After derivatization including methylation and acetylation, gas chromatography-mass spectrometry (GC-MS) was performed for glycosidic linkage information analysis of PAPS2.…”
Section: Methodsmentioning
confidence: 99%